Prywatne publicznym. O praktyce badań nad architekturą mieszkalną i zamieszkiwaniem: dom – człowiek – rzecz - Korduba, Piotr; Paradowska, Aleksandra (Artium Quaestiones, 2025)
In this article, we present the research method we developed in two books devoted to the villa architecture of Poznań. The houses in which we are interested, built in the interwar period, are viewed in the context of their social functioning and the material culture associated with them. We reflect on the public-private dichotomy, while at the same time attempting to break the ‘silence of the house’ and reveal what is hidden inside it. For this purpose, we focus not only on the surviving buildings and construction documentation, but also on documents relating to the social dimension of the house: land registry data, registration books, address books, written memoirs, diaries, correspondence, family photographs, and eyewitness accounts. Our goal is to answer questions both about the past and about changes in architecture over the decades. We refer to various perspectives and methodological concepts. We start from a “spatial turn”, conceiving the house as a frame in which history takes place. Following Karl Schloegel’s research, we focus on the interior, which allows us to learn about the history of specific people and social groups on the one hand, and the objects that accompany them on the other. In the first of these areas, the spatial turn is combined in our research with oral history. Witness accounts that we incorporate cover a whole range of statements, spanning the territory straddling storytelling and life writing. In the second area, we trace the biography of various, broadly understood objects: architecture, everyday items and photographs, presenting them as active actors in history, directly linked to people’s lives. We present the method we use in one of the chapters of our book.